Diagnostic testing: therapeutic mobilities, social fields, and medical encounters in the transnational healthcare practices of Polish migrants in the UK - Giuseppe Troccoli; Chris Moreh; Derek McGhee; Athina Vlachantoni (Elsevier, 2022)
While diagnostic tests are a fundamental component of contemporary medical practice they are seldom considered in studies of transnational healthcare. This article investigates the little-studied role played by diagnostic testing in the healthcare-seeking practices of migrants. It is concerned with the experiences of Polish migrants living in the UK and who access a variety of health services in their host and origin countries across the public and private sectors. We analyse data from semi-structured phone interviews conducted in 2020 with 32 adult Poles living in the UK who identified as having themselves, or non-professionally caring for someone with, a long-term health condition. The article contributes to the literature on migrants' transnational healthcare practices by showing the centrality of diagnostic technology in their health management and sense-making through the creation, modification, and maintenance of 'transnational social fields' (Levitt and Schiller 2004). By emphasizing the role of tests in the patient-doctor relationship the article exposes the therapeutic outcomes of the mobilities of patients and tests as they intersect with physicians in multiple medical encounters.